An efficient synthesis of novel sulfonyl[3.3.3]heteropropellanes from sulfonylacetamidines and ninhydrin-malononitrile adduct. (4th May 2017) - Nematpour, Manijeh; Abedi, Elahe
ABSTRACT: The synthesis in good yields of a novel class of sulfonyl[3.3.3]heteropropellanes via a one pot, five-component reaction between sodium arylsulfinates, trichloroacetonitrile, primary amines, and the malononitrile-ninhydrin adduct in H2 O at room temperature has been reported. GRAPHICAL ABSTRACT: